Basic psychological needs theory: research & application - Syed Hassan, Sharifah Sariah (IIUM Press, 2017)
This book has been compiled based on the research work written by the sole author Dr Sharifah Sariah Syed Hassan. The contributions of the content include the motivational theories and framework. The implementation of motivational theories in classroom context has been explored and discussed. The empirical evidence on the research framework has also been elaborated. Thus, this book provides a benchmark for future researches in giving guidelines for thesis and directed research writing. This book is handy and useful for light reading and further discussions in advanced statistical procedure such as Structural Equation Modeling. This book has originally been written in 2006. It was further enhanced and updated to sequence the chapters for the guidelines and references for students who want to carry out Structural Equation Model analyses and related research to Self Determination Theory and Basic Psychological Needs Theory.